My family for the war - Voorhoeve, Anne C. (New York : Dial Books, 2012)
Ten-year-old Franziska Mangold escapes Nazi Germany on the kindertransport she boards in Berlin, and when she arrives in London, she takes on the name Frances and struggles with her identity as she pieces together a new life without her family.
Young Adult.
Young Adult
Keywords: Holocaust, Jewish (1939-1945) -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Jews -- England -- Juvenile fiction; Refugees -- Juvenile fiction; World War, 1939-1945 -- England -- Juvenile fiction; Historical fiction; Holocaust, Jewish (1939-1945) -- Fiction; Identity -- Fiction; Jews -- England -- Fiction; Refugees -- Fiction; World War, 1939-1945 -- England -- Fiction; Historical fiction; Holocaust, 1939-1945 -- Fiction; Identity (Psychology) -- Fiction; Jews -- England -- Fiction; Refugees -- Fiction; World War, 1939-1945 -- England -- Fiction; Great Britain -- History -- George VI, 1936-1952 -- Juvenile fiction; Great Britain -- History -- George VI, 1936-1952 -- Fiction; Great Britain -- History -- 19th century -- Fiction; Historical fiction